The Clinical Impact of Methotrexate-Induced Stroke-Like Neurotoxicity in Paediatric Departments: An Italian Multi-Centre Case-Series - Santangelo, Andrea; Bartolini, Emanuele; Nuzzi, Giulia; Foiadelli, Thomas; Michev, Alexandre; Mina, Tommaso; Trambusti, Irene; Fichera, Valeria; Bonuccelli, Alice; Massimetti, Gabriele; Peroni, Diego G.; De Marco, Emanuela; et al. (Frontiers in Neurology, 2022)
Introduction: Stroke-like syndrome (SLS) is a rare subacute neurological complication of intrathecal or high-dose (>500 mg) Methotrexate (MTX) administration. Its clinical features, evoking acute cerebral ischaemia, with fluctuating course symptoms and a possible spontaneous resolution, have elicited interest among the scientific community. However, many issues are still open on the underlying pathogenesis,  clinical and therapeutic management and long-term outcome. Materials and methods: We retrospectively analysed clinical, radiological and laboratory records of all patients diagnosed with SLS between 2011 and 2021 at 4 National referral centres for Paediatric Onco-Haematology. Patients with  a latency period that was longer than 3 weeks between the last MTX administration of MTX and SLS onset were excluded from the analysis, as were those with unclear aetiologies. We assessed symptom severity using a dedicated arbitrary scoring system. Eleven patients were included in the study. Results: The underlying disease was acute lymphoblastic leukaemia type B in 10/11 patients, while fibroblastic osteosarcoma was present in a single subject. The median age at diagnosis  was 11 years (range 4-34), and 64% of the patients were females. Symptoms occurred after a mean of 9.45 days (± 0.75) since the last MTX administration and lasted between 1 and 96 hours. Clinical features included hemiplegia and/or cranial nerves palsy, paraesthesia, movement or speech disorders, and seizure. All patients underwent neuroimaging studies (CT and/or MRI) and EEG. The scoring system revealed an average of 4.9 points (± 2.3), with a median of 5 points (maximum 20 points). We detected a linear correlation between the severity of the disease and age in male patients. Conclusions: SLS is a rare, well-characterized complication of MTX administration. Despite the small sample, we have been able to confirm some of the previous findings in literature. We also identified a linear correlation between age and severity of the disease, which could improve future clinical management.